2018
DOI: 10.7754/clin.lab.2017.170930
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of IL-35 and Gene Expression of FoxP3 in Coronary Artery Disease: Is There Any Interplay Between Them and 25-Hydroxyvitamin D3?

Abstract: It appears that reduced mRNA expression of FoxP3 and circulating level of IL-35 are of significance in the context of CAD pathogenesis. However, more studies are required to elucidate underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Moreover, we showed previously in the same population and setting that the level of 25(OH)D was significantly lower in CAD patients compared to control group [7,8,41]. Also, the serum level of 25(OH)D was not significantly correlated with the number of diseased vessels as a representative of the extent of cardiac involvement [7,8] which is in accordance with our findings in this study. It is noteworthy that serum levels of 25(OH)D for almost all of our patients (98.5%) was lower than recommended ranges for general population and especially for cardiovascular patients [42].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, we showed previously in the same population and setting that the level of 25(OH)D was significantly lower in CAD patients compared to control group [7,8,41]. Also, the serum level of 25(OH)D was not significantly correlated with the number of diseased vessels as a representative of the extent of cardiac involvement [7,8] which is in accordance with our findings in this study. It is noteworthy that serum levels of 25(OH)D for almost all of our patients (98.5%) was lower than recommended ranges for general population and especially for cardiovascular patients [42].…”
Section: Plos Onesupporting
confidence: 92%
“…Some studies have addressed this and a study by Bodnar et al showed that long-term storage over 40 years even if deteriorate 25 (OH)D somewhat, it did so similarly across samples [44]. We did not find the level of 25(OH) D in our samples to be lower compared to our fresh samples in our other studies at the same hospital [7,8,41]. Regardless, as the samples are at the same age and have been stored in the same conditions, the impact if any is expected to be the same for all and would not change their association of vitamin D/ telomerase with the outcome.…”
Section: Plos Onecontrasting
confidence: 62%
See 2 more Smart Citations
“…Studies have shown that overexpression of IL-1 can induce the release of higher levels of IL-23 by hepatocytes and macrophages, and cause disorders of lipid metabolism, triggering formation of an inflammatory microenvironment ( 16 , 17 ). It was also reported that IL-23 is overexpressed in local tissues of atherosclerotic plaques, while IL-35 expression is low, suggesting that IL-23 and IL-35 are associated with the formation of atherosclerotic plaques ( 18 , 19 ). In this study, the results showed that high expression of MDA and low expression of SOD were not only associated with the formation of atherosclerotic plaques, but also associated with the severity of the lesions, suggesting that abnormal expression of both markers may have some auxiliary significance for judging the extent of lesions, and can promote onset and progression of coronary heart disease.…”
Section: Discussionmentioning
confidence: 96%